2013
DOI: 10.1093/fampra/cmt074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a specialist nurse-led hypertension clinic with consultant backup in two inner city general practices: randomized controlled trial

Abstract: Invitation to a specialist nurse-led hypertension clinic with consultant back up was associated with reduced systolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Two UK research studies on specialist clinics published from 2010 onwards were identified from the mapping review. 219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study.…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Two UK research studies on specialist clinics published from 2010 onwards were identified from the mapping review. 219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study.…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
“…219,220 One of the clinics was for patients with hypertension 219 and one was for high-risk respiratory patients with COPD or asthma. 220 The research studies were both quantitative: one was a RCT 219 and the other was an uncontrolled observational study. 220 A summary table of the included studies is provided (see Appendix 4, Table 31).…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
“…14 MI has been associated with decreases in SBP by 4mmHg and DBP by 3mmHg as compared to usual care in randomized control trials. 14,15 MI has also been associated with long term changes over greater than one year. 16 Interviews of patients demonstrated that staff trained in MI were more engaged in encounters, and patients felt guided and motivated rather than directed.…”
Section: Evidence For the Problemmentioning
confidence: 99%
“…13 However, studies using registered nurses have also demonstrated decreased blood pressure in patients. 14,15,19 Other studies using medical assistants (MA) or layperson health coaches have shown promise. While the use of MA-driven protocols have not been associated with improvements in blood pressure, improvements in other health outcomes such as reduced hemoglobin A1C to 8.0% or normal low-density lipoprotein levels have been shown.…”
Section: Evidence For the Problemmentioning
confidence: 99%
See 1 more Smart Citation